Thoracophagus Conjoint Twins: A Case Report - Paudel, Dipesh; Dhakal, Radha Devi; Adhikari, Deepak (Journal of Chitwan Medical College, 2019)
A 27 years old primigravida woman at 19 weeks of gestation was came for routine antenatal checkup in Chitwan Medical College was diagnosed as twin pregnancy with thoracophagus conjoined twin. The fetal biometrics of both were consistent with the gestational age. Fetuses were found with fusion of the skin contour, at the level of the lower chest with complex appearing fused cardiac near midline and liver appears separate. Both fetal heads were in breech presentation facing faces with each other at the same level. Bilateral upper and lower limbs were identified in both fetuses with same gender. The parents decided to terminate the pregnancy but refused autopsy.